Continuum model for masonry: Parameter estimation and validation - Lourenço, Paulo B. (1998)
A novel yield criterion that includes different strengths along each material axis is presented. The criterion includes two different fracture energies in tension and two different fracture energies in compression. The ability of the model to represent the inelastic behavior of orthotropic materials is shown, and a set of experimental tests to characterize the constitutive behavior of masonry is proposed. The capability of the model to reproduce the strength behavior of different masonry types is demonstrated through a comparison with available experimental data in masonry panels subjected to uniform biaxial loading conditions. Finally, the model is validated against experimental results on masonry shear walls and good agreement is found. A clear understanding of the behavior of masonry sheer walls, and the nonlinear phenomena involved in its collapse, is presented with the help of a detailed comparison between numerical and experimental results.